The Preference of Children and their Parents About the Pediatric Dentist's Appearance - Luiz Evaristo Ricci Volpato; Lucilene Abigail dos Santos; Ivan Onone Gialain; Ana Thereza Saboia de Campos Neves; Andreza Maria Fabio Aranha (Association of Support to Oral Health Research (APESB), 2021)
Objective: To analyze whether children and their parents prefer a particular professional coat worn by the dentist and whether these preferences are influenced by their gender or level of anxiety. Material and Methods: Standardized images of male and female models dressed with different coats were shown to 400 pairs of 5-12 year-old children and respective parents and they were asked to point their preference. Information about child's dental experience was collected and children's anxiety level was obtained using the Children's Fear Survey Schedule-Dental Subscale. Results: Both children (55.5%) and parents (76.5%) preferred a female professional over a male one. Children preferred the dentist wearing a white coat, while adults preferred the dentist wearing a colored coat (p<0.05). There was a tendency for the child to choose a dentist with the same gender as theirs, so boys chose more male dentists and girls more female dentists (p<0.05), but there was no difference between the choice of the dentist's coat between boys and girls (p=0.53). Conclusion: Children have strong preferences in relation to the appearance of their dentists. Children and parents preferred female dentists, but there was a tendency to choose the dentist with the respondent's gender. Contrary to popular belief, children preferred their dentists wearing the conventional white coat, different from their parents who preferred dentists wearing a colored coat.